ANALISIS DAY OF THE WEEK EFFECT DAN ROGALSKI EFFECT PADA SAHAM INDEKS LQ45 - Tatang Hendranata (Parsimonia - Jurnal Ekonomi dan Bisnis, 2015)
There are still many researches which have various findings on the emergence of efficient market hypotheses through market anomaly tests. This research is conducted to identify efficient market anomaly, especially day of the week effect and rogalski effect in Indonesian stock market within 2013 – 2014 period. The research also uses trading volume to investigate the day of the week effect and the rogalski effect. The research uses ANOVA, Pearson correlation, and independent sample t tests. The research results show that Monday return is negative. It is the lowest market value in a week. Thus, it is concluded that a day of the week effect is applied on LQ45 stocks. The relation between trading volume and return is weak but positive. It means that one variable increase affect the other variable increment. The research does not find any rogalski effect in LQ45 stocks since there is an external negative sentiment that influence return within the research period.